2008
DOI: 10.1002/pmh.43
|View full text |Cite
|
Sign up to set email alerts
|

Tattoos and antisocial personality disorder

Abstract: Objective The relationship of tattoos to the diagnosis of antisocial personality disorder (ASPD) was explored in a forensic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 23 publications
0
13
0
3
Order By: Relevance
“…Američko istraživanje pokazalo je da su osobe s tetovažama koje pristupaju američkoj vojsci sklonije konzumaciji većih količina alkohola, pušenju cigareta, ali i rizičnom ponašanju kao što je vožnja s vozačem pod utjecajem alkohola (23). Povišena impulzivnost i rizično ponašanje nađeni su u vojnika s tetovažama i u toj skupini više je bolesnika dijagnosticirano s antisocijalnim poremećajem ličnosti u usporedbi s vojnicima bez tetovaža (24,25).…”
Section: Types Of Tattoosunclassified
See 1 more Smart Citation
“…Američko istraživanje pokazalo je da su osobe s tetovažama koje pristupaju američkoj vojsci sklonije konzumaciji većih količina alkohola, pušenju cigareta, ali i rizičnom ponašanju kao što je vožnja s vozačem pod utjecajem alkohola (23). Povišena impulzivnost i rizično ponašanje nađeni su u vojnika s tetovažama i u toj skupini više je bolesnika dijagnosticirano s antisocijalnim poremećajem ličnosti u usporedbi s vojnicima bez tetovaža (24,25).…”
Section: Types Of Tattoosunclassified
“…S druge strane, ima istraživača koji pokazuju da je tetovira-like riding in a car driven by a person under the influence of alcohol (23). Increased impulsiveness and risky behaviour have been identified in soldiers with tattoos, and the same group contained more patients diagnosed with antisocial personality disorder than the group of soldiers without tattoos (24,25).…”
Section: Types Of Tattoosmentioning
confidence: 99%
“…In a nationally representative sample of German residents, those with tattoos feel significantly worse in terms of mental health than non‐tattooed respondents . Significantly more residential psychiatric patients with tattoos had personality disorders compared to patients without tattoos …”
Section: Introductionmentioning
confidence: 95%
“…9 Significantly more residential psychiatric patients with tattoos had personality disorders compared to patients without tattoos. 12 Tattoos have historically been associated with various sociodemographic characteristics and risky health behaviors. 13 For example, tattoos are linked with being male, 14 illicit drug use, 15,16 tobacco use, 13 alcohol and marijuana use, 17 binge drinking, 13,15 underlying psychopathological disorder, 18 military service, 19 engaging in earlier and/or more frequent sexual activity with a greater number of partners, 15,[20][21][22] gang-related activity, 23 and being arrested.…”
Section: Introductionmentioning
confidence: 99%
“…Khosla, Joseph, and Gordon (2010) noted that tattoos are more common in those who have psychiatric problems and who come into contact with mental health services. Cardasis, Huth-Bocks, and Silk (2008) found that patients in a forensic psychiatric unit with a diagnosis of antisocial personality disorder were more likely to have tattoos than other patients. Piercings and tattoos are often correlated with high-risk activities in college populations (Burger, 2002).…”
mentioning
confidence: 97%